MORPHOLOGICAL MEANS OF EXPRESSING THE CHRONOTOPE IN LANGUAGE AND TEXT - Zebo Pulatovna Aminova (International Journal of Literature and Language Studies, 2026)
The article examines morphological means of expressing the chronotope as a category reflecting the unity of temporal and spatial coordinates in language and text. Particular attention is paid to the functioning of verb forms, categories of tense, aspect, and mood, as well as nominal and adverbial means that ensure the representation of spatio-temporal relations. The study is based on functional-semantic and cognitive approaches, which make it possible to reveal the role of morphology in structuring artistic and discursive space. It is concluded that morphological means play a key role in shaping the chronotope as a text-forming category.